Current Situation and Development Prospects of Female Entrepreneurs Engaged İn Social Business İn Azerbaijan - Ulkar ZEYNALOVA; Ulkar BAYRAMOVA (Communications of International Proceedings, 2021)
Social business is a new and modern type of business that focuses on the essential needs of humanity, dividends and one whole social target. Social business does not aim to make a profit as a traditional business does, the main purpose of this job is to solve social problems by arranging the sale of products and services, utilizing business methods. The bigger the volume of the entrepreneurship is in a country's economy, it is considered that the stronger the economy of that country is. For this reason, many developing countries are paying great attention to the development of entrepreneurship. The development of social business in the country plays a significant role in eliminating unemployment and poverty, resolving social problems of society, improving small and medium enterprises and increasing the level of welfare. At the same time, one of such policies in the modern world is the growth and development of women's entrepreneurship. Women consititute 50.1% of the population of the Republic of Azerbaijan. This study examines the entrepreneurial activities of women, their role in development of social business and the problems they are facing. The article will look through social business, its types, as well as women's entrepreneurship not only theoretically, but also systematically. In addition, interviews will be conducted with female entrepreneurs engaged in social business in Azerbaijan, and analyzed. As a result, some recommendations will be given based on theory and research and development prospects will be indicated.
Keywords: Social Business; Women's Entrepreneurship; Welfare.